2013
DOI: 10.1177/1742715012468784
|View full text |Cite
|
Sign up to set email alerts
|

Combating infections at Maine Medical Center: Insights into complexity-informed leadership from positive deviance

Abstract: A case study of how the organizational change process known as Positive Deviance was used to fight healthcare-associated infections at Maine Medical Center highlights the human and social aspects of leadership in a complex adaptive system. It illustrates that leadership can shape selforganization in a manner that facilitates creative, productive, desirable outcomes. We found influential roles of anxiety, attachment, and relationships in facilitating organizational leadership. We describe how the process of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Chaos theory, in this sense, describes a mathematical concept that delineates how within different systems, patterns appear but in a random fashion. [16] Complexity theory is also useful for understanding nonlinear systems [13,19,20]. Similarly, complex systems have been described as exhibiting butterfly effects in which a small change in the system could potentially lead to a large change overall [12,13,19].…”
Section: Non-linear Distributive Pattern Formationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chaos theory, in this sense, describes a mathematical concept that delineates how within different systems, patterns appear but in a random fashion. [16] Complexity theory is also useful for understanding nonlinear systems [13,19,20]. Similarly, complex systems have been described as exhibiting butterfly effects in which a small change in the system could potentially lead to a large change overall [12,13,19].…”
Section: Non-linear Distributive Pattern Formationsmentioning
confidence: 99%
“…Granted, however, even though it may seem that self-organizing systems come free to organizations in which they do not need to be managed, this thinking is counter-intuitive. Lindberg and Schneider [20] identified that order is not free when talking about self-organizing systems. Instead, leadership must be able to achieve the right balance between equilibrium and chaos without hampering the emergent processes that come from self-organizing systems [20].…”
Section: The Role Of Leadershipmentioning
confidence: 99%
See 2 more Smart Citations
“…Social occurrences, including organizations, became the subject of research utilizing the methods and principles of complexity theory in the early 1990s . Later, complexity theorists developed the concept of complex adaptive systems (CAS) . Although originally used by researchers in the natural sciences, complexity theory is nowadays increasingly applied to analyse social organizations .…”
Section: Introductionmentioning
confidence: 99%